qDTY introgression to improve the drought tolerance of Taiwanese japonica rice variety Tainan 11 - Bordeos, Alicia; Henry, Amelia; Pocsedio, Arnel; Dixit, Shalabh; Lai, Ming-Hsin; Leung, Hei (Informa UK Limited, 2025)
Whereas many indica and rainfed rice-growing regions have historically been considered drought-prone, lowland japonica-growing regions have typically not been considered to be affected by drought. However, the increasing incidence of drought in japonica rice-growing regions necessitates breeding for future climate scenarios. Several major-effect drought tolerance yield QTLs (qDTYs) have been introgressed into indica backgrounds, but further improvement of japonica varieties is now needed. In this study, we introgressed seven qDTYs and their combinations through crossing four qDTY donor lines with the Taiwanese japonicavariety Tainan 11 (TN 11). BC3F6- BC3F8 progeny were evaluated in agronomic trials under drought. Although no single group of introgression lines with the same qDTY stood out as best performing, we observed that the higher yield under drought appeared to correspond with earlier time to flowering. Selected lines for yield under drought showed similar height and grain type to TN 11. We identified three lines that could be evaluated for deployment in Taiwan or as pre-breeding material for developing other drought-tolerant japonica varieties.